Identification of transport systems involved in eflornithine delivery across the blood-brain barrier - Christopher P. Watson; Gayathri Nair Sekhar; Sarah A. Thomas (Frontiers Media S.A., 2023)
Human African Trypanosomiasis (HAT) is a neglected parasitic disease that continues to persist in sub-Saharan Africa. It is fatal if untreated. The first stage of the disease is associated with the presence of the parasite in the periphery and the second stage with the presence of the parasites in the CNS. The treatment of CNS stage HAT requires the drugs to cross the blood-brain barrier (BBB). Eflornithine is an amino acid analogue that is used to treat second stage HAT gambiense both alone and in combination with nifurtimox. Recent studies have identified that accumulation of eflornithine into the parasites (trypanosomes) involves the amino acid transporter (Trypanosoma brucei AAT6). In this study we tested the hypothesis that eflornithine uses a cationic amino acid transport system to cross the BBB. We particularly focused on system y+ and system B0,+. To do this we utilized specialist databases to compare the physicochemical characteristics of relevant molecules and an in vitro model of the BBB to explore the mechanisms of eflornithine delivery into the CNS. Our results confirmed that eflornithine is related to the endogenous amino acid, ornithine. At pH 7.4, eflornithine is predominately (92.39%) a zwitterionic (dipolar) amino acid and ornithine is predominately (99.08%) a cationic (tripolar) amino acid. In addition, the gross charge distribution at pH 7.4 of eflornithine is much smaller (+0.073) than that of ornithine (+0.99). Further results indicated that eflornithine utilized a saturable transport mechanism(s) to cross the hCMEC/D3 cell membranes and that transport was inhibited by the presence of other amino acids including ornithine. Eflornithine transport was also sodium-independent and sensitive to a y+ system inhibitor, but not a B0,+ system inhibitor. Eflornithine transport was also inhibited by pentamidine, suggestive of transport by organic cation transporters (OCT) which are expressed in this cell line. We confirmed expression of the y+ system protein, CAT1, and the B0,+ system protein, ATB0,+, in the hCMEC/D3 cells. We conclude that eflornithine uses the cationic amino acid transporter, system y+, and OCT to cross the BBB. This research highlights the potential of system y+ to deliver drugs, including eflornithine, across the BBB to treat brain diseases.